2021
DOI: 10.1109/ms.2020.3023302
|View full text |Cite
|
Sign up to set email alerts
|

Serverless Applications: Why, When, and How?

Abstract: Serverless computing shows good promise for efficiency and ease-of-use. Yet, there are only a few, scattered and sometimes conflicting reports on questions such as Why do so many companies adopt serverless?, When are serverless applications well suited?, and How are serverless applications currently implemented? To address these questions, we analyze 89 serverless applications from open-source projects, industrial sources, academic literature, and scientific computing-the most extensive study to date. IEEE Sof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 8 publications
0
36
0
Order By: Relevance
“…Other works investigate the efficiency of serverless systems for different classes workloads, namely ML training [37], latency-critical microservices [38], data-intensive applications [39]- [41], and confidential computations [42]. Eismann et al categorizes open-source serverless applications according to their non-performance characteristics [43]. Shahrad et al analyzes invocation frequency and execution time distributions of applications in Azure Functions and explores the design space of function instance keep-alive policies [16].…”
Section: Related Workmentioning
confidence: 99%
“…Other works investigate the efficiency of serverless systems for different classes workloads, namely ML training [37], latency-critical microservices [38], data-intensive applications [39]- [41], and confidential computations [42]. Eismann et al categorizes open-source serverless applications according to their non-performance characteristics [43]. Shahrad et al analyzes invocation frequency and execution time distributions of applications in Azure Functions and explores the design space of function instance keep-alive policies [16].…”
Section: Related Workmentioning
confidence: 99%
“…The cost effectiveness of FaaS for low-rate and bursty computations has been observed and reported by various studies [42,66,67] and has been leveraged by frameworks like LI-BRA [103] and Spock [76]. This unique FaaS economic model has revenue and performance implications for both the cloud provider and the application developer.…”
Section: Serverless Economic Modelmentioning
confidence: 98%
“…Server-less computing is any computing platform that hides server usage from developers and runs code on-demand automatically scaled and billed only for the time the code is running [4]. Based on Eismann, et al [5] analysis of 89 server-less applications, they find that the most commonly reported reasons for the adoption of server-less are to save costs for irregular or bursty workloads, to avoid operational concerns, and for the built-in scalability. Serverless applications are most commonly used for short-running tasks with low data volume and bursty workloads but are also frequently used for latency-critical, high-volume core functionality.…”
Section: State Of the Art In Software Architecturementioning
confidence: 99%